Front Cover: Mix‐&‐Read Determination of Mercury(II) at Trace Levels with Hybrid Mesoporous Silica Materials Incorporating Fluorescent Probes by a Simple Mix‐&‐Load Technique (ChemistryOpen 12/2018). Issue 12 (3rd December 2018) - Climent, Estela; Hecht, Mandy; Witthuhn, Heike; Gawlitza, Kornelia; Rurack, Knut
Abstract : The Front Cover shows how differences in color and fluorescence on a test strip can be easily read out with a mobile device. Two reference spots frame the sensitive spot that indicates the presence of trace amounts of Hg II below the threshold in a natural water sample. This dipstick contains a hybrid material that combines boron‐dipyrromethene (BODIPY) probes sterically loaded into specifically tailored mesoporous silica particles, allowing for ultrasensitive Hg II detection through enhanced fluorescence within a few seconds. More information can be found in the Full Paper by K. Rurack and co‐workers onpage 957 in Issue 12, 2018 (DOI:10.1002/open.201800277 ).